2009
DOI: 10.1016/s0140-6736(09)60484-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative radiotherapy versus selective postoperative chemoradiotherapy in patients with rectal cancer (MRC CR07 and NCIC-CTG C016): a multicentre, randomised trial

Abstract: SummaryBackgroundPreoperative or postoperative radiotherapy reduces the risk of local recurrence in patients with operable rectal cancer. However, improvements in surgery and histopathological assessment mean that the role of radiotherapy needs to be reassessed. We compared short-course preoperative radiotherapy versus initial surgery with selective postoperative chemoradiotherapy.MethodsWe undertook a randomised trial in 80 centres in four countries. 1350 patients with operable adenocarcinoma of the rectum we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
821
3
43

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,331 publications
(891 citation statements)
references
References 44 publications
24
821
3
43
Order By: Relevance
“…Also, downstaging may have occurred after preoperative treatment with chemoradiotherapy or after preoperative short‐course radiotherapy followed by a long interval to surgery 39. However, the majority of patients in this database that received short‐course radiotherapy had surgery within an interval of 10 days after preoperative therapy, and downstaging is not observed in this group 40, 41. Most importantly, postoperative staging is the gold standard and clinical staging using CT and MRI is rather unreliable, especially regarding lymph node staging 18, 42…”
Section: Discussionmentioning
confidence: 88%
“…Also, downstaging may have occurred after preoperative treatment with chemoradiotherapy or after preoperative short‐course radiotherapy followed by a long interval to surgery 39. However, the majority of patients in this database that received short‐course radiotherapy had surgery within an interval of 10 days after preoperative therapy, and downstaging is not observed in this group 40, 41. Most importantly, postoperative staging is the gold standard and clinical staging using CT and MRI is rather unreliable, especially regarding lymph node staging 18, 42…”
Section: Discussionmentioning
confidence: 88%
“…A Medical Research Council (MRC) trial including 1,350 patients demonstrated a significant reduction of local recurrence in patients receiving preoperative scRT compared with initial surgery with selective postoperative radiochemotherapy (4.4% versu 10.6% after 3 years). In addition, a relative improvement in diseasefree survival has been shown, whereas overall survival did not differ between the groups [33]. A number of randomised trials demonstrated the effectiveness of CRT (either post-or preoperatively).…”
Section: Patient Selection and Neoadjuvant Therapymentioning
confidence: 99%
“…It is accepted that preoperative radiotherapy is more efficacious than postoperative (adjuvant) treatment at achieving local control [24,25]. The two widely accepted approaches to preoperative treatment are either short course preoperative radiotherapy (SCPRT) or long course chemoradiotherapy (CRT).…”
Section: The Role Of Preoperative Neoadjuvant Therapymentioning
confidence: 99%
“…The rational for SCPRT for most patients are the results of three large European trials [26][27][28] and the UK's CR07 trial [24] that reported improved local control and possibly improved survival for rectal cancer patients treated with SCPRT against those treated with surgery alone. However, some of these trials have been criticised for the lack of TME surgical resection in the surgery arm and the benefit observed has been labelled secondary to the effect of RT compensating for poor surgical quality.…”
Section: The Role Of Preoperative Neoadjuvant Therapymentioning
confidence: 99%